Pengendalian Persediaan Suplemen Kesehatan Pada Masa Pandemi Dengan Menggunakan Metode ABC,EOQ,ROP Di Apotek Karang Langit Lamongan Tahun 2021Pe - Mila Apriani Hamidah; Anindi Lupita Nasyanka; Norainny Yunitasari (Universitas Muhammadiyah Gresik, 2022)
The COVID-19 outbreak has greatly impacted all sectors, one of which is the increasing number of requests for health supplements to strengthen the immune system from viral attacks. This causes frequent shortages of health supplement stocks in several pharmacies. The purpose of this study was to analyze the implementation of health supplement inventory planning control at Apotek Karang Langit Lamongan by comparing the results of secondary data using the ABC, EOQ, ROP methods. This research is observational with quantitative descriptive data analysis. Data collection is retrospective and the research instrument is a data collection sheet. The results showed that there were 20 types of health supplements in group A (20%) with an income value of Rp. 35,203,380 (69.24%) of the total income. Group B consisted of 33 species (30%) with an income value of Rp. 10,469,200 (20.59%) of the total income. Group C consisted of 55 species (50%) with an income value of Rp. 5,167,585,8 (10,17%) of the total income. Health supplement control is prioritized in group A. In the calculation of EOQ group A starting from 1-152 items and ordering frequency in 3 months as much as 5-23 times, for group B starting from 1-210 items with ordering frequency between 3-5 times, group B starts from 1-210 items with ordering frequency between 3-5 times, C ranging from 1-160 items with a frequency of orders between 1-3 times. ROP group A starts from 1-58 items, for group B starts from 0-52 items and in group C starts from 0-22 items. Therefore, the results of the ABC method analysis, EOQ, SS, ROP calculations can be used to control the planning of health supplement procurement at Karang Langit Pharmacy. Keywords: control, health supplement planning, ABC analysis, EOQ, SS, ROP.